Evidence for student-centered teaching: A process evaluation of MTB-MLE classroom instruction - Narvacan, Cristian (Papanda Publisher, 2023)
Over a decade into the implementation of Mother Tongue-Based Multilingual Education (MTB-MLE) in the Philippines, program implementers continue to encounter challenges, especially in terms of student-centered instruction (SCI). To ensure a student-centered program, the Department of Education crafted guiding principles to which MTB-MLE teaching and learning should be anchored. However, numerous implementation challenges could potentially affect the application of SCI in the classroom. Utilizing process evaluation adopted from Stufflebeam's (2000) CIPP model, this study investigated the extent to which MTB-MLE teachers carry out SCI in a public elementary school. This paper also examined teachers' challenges and coping strategies in relation to classroom instruction. Results revealed that SCI was strongly implemented in the MTB-MLE classes. Further, the following SCI-related challenges emerged: (1) learners' unruly behavior during activities; (2) difficulty in the use of mother tongue; and (3) lack of cooperation among students. To address these concerns, the teachers employed coping strategies, such as setting clear classroom rules, using translation and code-switching, and providing varied activities to match learners' interests. The findings of this paper may aid policymakers, curriculum designers, and school administrators in developing appropriate programs and activities aimed at enhancing teachers’ competence to implement a student-centered MTB-MLE education.